Area Deprivation Index as a predictor of economic risk and social and neighborhood perceptions among families enrolled in Early Head Start. (June 2022) - Hooper, Alison; Hustedt, Jason T.; Slicker, Gerilyn; Hallam, Rena A.; Gaviria-Loaiza, Juana; Vu, Jennifer A.; Han, Myae
Highlights: The Area Deprivation Index is an efficient tool for gathering neighborhood-level data among Early Head Start families. Families in more disadvantaged neighborhoods were more likely to report experiencing economic hardship and economic pressure. Neighborhood disadvantage was negatively correlated with families' perceived social status in the United States. Higher neighborhood disadvantage was associated with the perception of neighborhoods as being less safe. Abstract: Previous research suggests that aggregate neighborhood-level measures of socioeconomic disadvantage are related to social and medical outcomes. To date, these measures have primarily been used in health-related research, with far fewer applications to developmental psychology and education. This study used a measure of neighborhood socioeconomic disadvantage, the Area Deprivation Index, to examine relationships between neighborhood disadvantage, family risk factors, and perceptions of neighborhood safety, social cohesion, and social status in Early Head Start families. Results suggest that neighborhood disadvantage is important to consider in efforts to support the health and well-being of low-income families with young children and that the Area Deprivation Index is appropriate for this use. Neighborhood disadvantage predicted economic hardship and pressure, perceived neighborhood safety and social cohesion, and subjective social status. This has implications for planning and implementation of family supports offered through programs like Early Head Start.